Constituents and antibacterial activity of leaf essential oil of Plectranthus scutellarioides. (2nd November 2021) - Aziz, Pakeeza; Muhammad, Nadeem; Intisar, Azeem; Abid, Muhammad Amin; Din, Muhammad Imran; Yaseen, Muhammad; Kousar, Rehana; Aamir, Aqsa; , Quratulain; Ejaz, Rabia
Abstract: This study covers chemical profiling of leaf essential oil of Plectranthus scutellarioides (L.) R.Br along with the first report on its antibacterial activity. The extraction was performed by microwave assisted hydrodistillation where the yield of essential oil was 0.18%. A total of 28 constituents were separated and identified by gas chromatography mass spectrometry. The constituents that occurred in abundance were spathulenol (24.57%), D-germacrene (14.53%), bicyclogermacrene (11.24%), nonacosane (9.74%) and morillol (4.95%). The antibacterial evaluation of essential oil was carried out against 8 different gram negative and positive strains including multidrug-resistant ones with agar well diffusion method and macrodilution method and was found to be active against all strains. The strongest activity (MIC) was found against multidrug resistant strains of Escherichia coli (0.625 mg/mL) and methicillin resistant Staphylococcus aureus (2.5 mg/mL) that shows the potential of this essential oil. Abstract : UF0001